Effect of Exosomal Protein Expression and Electrochemical Nano Interface in Morphine Analgesia Tolerance - Lyu, Ning; Li, Xiaoyun (Cellular and Molecular Biology, 2022)
The current understanding of neurons cannot well explain the phenomenon of morphine tolerance, and even if some neuronal drugs are used in combination with morphine, they cannot achieve good results. In recent years, exosomal proteins have been the role of morphine tolerance and morphine-induced hyperalgesia is becoming more and more important. In clinical application, a larger dose is needed to achieve the desired analgesic effect, and large doses of morphine will aggravate the adverse drug reactions. The purpose of this experiment is to explore the role and mechanism of exosomal protein expression and electrochemical nanointerface in morphine analgesic tolerance and provide a theoretical basis for the application of exosomal protein in the clinical prevention and treatment of morphine tolerance. In this paper, adult male rats were randomly divided into groups and analyzed from four aspects: enhancing the analgesic effect of high-dose morphine, preventing morphine tolerance, the effect of morphine-induced hyperalgesia, and changes in mRNA levels of related genes. Experiments have shown that the mRNA levels of exosomal protein-related genes in the spinal cord of morphine-tolerant rats are significantly increased, and the rats given exosome protein inhibitors can prolong morphine analgesia and relieve morphine tolerance and hyperalgesia in behavior. It can inhibit the increase of exosomal protein-related genes. It shows that low-dose long-term morphine treatment can cause spinal endoplasmic reticulum stress, and the exosomal protein inhibitor 4-PBA or TUDCA can enhance the analgesic effect of morphine in neuropathic pain.